Investimento em segurança pública nos estados do norte e nordeste do Brasil: uma análise da eficiência técnica para o ano de 2021 - Diniz, Daleth Cecília da Costa (Brasil, 2024)
The present study aimed to use the Data Envelopment Analysis (DEA) methodology through the DEAP software to analyze the technical efficiency of public security in the North and Northeast regions of Brazil. The research focused on outputs (products) and considered the states as Decision Making Units (DMUs), taking into account rates of thefts and robberies, as well as rates of violent deaths, which were transformed into their inverses, as they were considered undesirable outputs. This allowed for the evaluation of the efficiency of public security in the states. The obtained results revealed that, out of the 16 states analyzed in the North and Northeast regions, 4 states were considered efficient in terms of resource allocation in public security: Acre, Maranhão, Paraíba, and Piauí. These states demonstrated better performance in relation to theft and robbery rates, as well as violent death rates, compared to the other states. These results highlight the importance of identifying good practices and efficient strategies used by the efficient states, in order to serve as references for the other states. Furthermore, the efficiency analysis through DEA using the DEAP software allowed for identifying improvement opportunities in the states that did not achieve efficiency and pointed to the need for policy revisions and resource allocation in public security. The obtained results provide valuable information for public managers and policymakers in the pursuit of more efficient and effective strategies in combating crime and promoting security for the population.